MOBILE-BASED E-WALLET PROTOTYPE TO SUPPORT ELECTRONIC PAYMENTS IN CAMPUS ENVIRONMENT - Ghifari Munawar; Firiontina Argan Dini H (Jurnal Mantik, 2022)
Electronic wallets (e-wallets) are currently considered to solve problems that often arise from the use of cash, especially in terms of convenience and security in transactions. The application of e-wallets in the campus environment is still rare, even if there is usually a third-party (non-official) provider. Many students using cash as a payment instrument on campus can be at risk of transmitting the COVID19 virus and other diseases, so there is an urgency to use other alternative mechanisms. This study aims to design a mobile-based e-wallet prototype that can specifically handle electronic payment transactions in the campus environment. Especially single tuition payments (UKT), payments at public service places (cooperatives, canteens, photocopying places), and fundraising for donations or events by using the QR Code as the transaction medium. System requirements exploration is carried out through questionnaires distributed to target users (students) to get a list of functional requirements. The method used in developing the application is an iterative rational unified process (RUP) model, which divides the stages into inception, elaboration, construction, and transition phases. In its implementation, the application is developed on the Android SDK mobile platform as a front-end technology using a model view presenter (MVP) architecture and the Laravel web framework as back-end technology. The e-wallet prototype that has been developed is then tested for functionality and evaluated based on user experience testing using the user experience questionnaire (UEQ) method. Based on the results of the UEQ measurements that have been made to the respondents, a positive evaluation was obtained with a value of over 0.8. This means that the prototype that has been developed is good in terms of attractiveness, functionality, display design, and comfort of use.